Future of ACP-EU trade relations : an overview of the forthcoming negotiations - Bilal, Sanoussi (ECDPM MaastrichtNL, 2002)
Considers three main issues viz. possible common trade interests of the ACP group; possible configurations of ACP groupings for negotiations with the EU; and, the need to strengthen the capacities of ACP countries to participate in the negotiations.